2022
DOI: 10.4103/aam.aam_65_21
|View full text |Cite
|
Sign up to set email alerts
|

The ambulatory blood pressure monitoring among obese and nonobese diabetes mellitus patients

Abstract: Background: Obesity and diabetes mellitus are two major factors related with the risk of metabolic syndrome and cardiovascular diseases. Co-existing hypertension with diabetes mellitus and obesity has poor prognosis for cardiovascular diseases. Ambulatory blood pressure monitoring (ABPM) correlates more closely to target organ damage than clinic blood pressure. Objectives: The objective of the study is to assess and compare ABPM pattern among obese and nonobese diabetes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Conversely, among participants with coexisting hypertension and diabetes, no significant difference was observed in nocturnal SBP values, regardless of obesity status. When categorizing participants based on BMI values (above 25 and below 25), Mathews et al demonstrated elevated diurnal systolic blood pressure variability (calculated as standard deviation > 10 mm Hg) among obese subjects, with no statistically significant difference noted in diastolic blood pressure variability within these same groups [20]. Palatini et al also reported a relationship between the BMI of untreated hypertensive participants and the variability in the systolic and DBP during the night [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, among participants with coexisting hypertension and diabetes, no significant difference was observed in nocturnal SBP values, regardless of obesity status. When categorizing participants based on BMI values (above 25 and below 25), Mathews et al demonstrated elevated diurnal systolic blood pressure variability (calculated as standard deviation > 10 mm Hg) among obese subjects, with no statistically significant difference noted in diastolic blood pressure variability within these same groups [20]. Palatini et al also reported a relationship between the BMI of untreated hypertensive participants and the variability in the systolic and DBP during the night [26].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, another study emphasized that obesity plays a crucial role in influencing ABPM values, affecting not only individuals with hypertension but also those with conditions like diabetes. In their study, Mathews et al revealed that individuals with both obesity and diabetes mellitus exhibited significant circadian variations in blood pressure parameters and an elevated prevalence of non-dipping status [20]. Our study aimed to evaluate the differences in the short-term blood pressure variability profile in both treated and drug-naive individuals with essential hypertension in different categories of obesity.…”
Section: Introductionmentioning
confidence: 92%